Sustained Resolution of Multifocal Low-Grade Dysplasia in Ulcerative Colitis. Issue 9 (September 2019) - Canakis, Andrew; Dellatore, Peter; Josephson, Matthew; Canakis, Justin; Alruwaii, Zainab; Lazarev, Mark; Brant, Steven R.
Abstract : ABSTRACT: In inflammatory bowel disease, prolonged disease duration, pancolitis, histological inflammation, and subsequent dysplasia are associated with an increased risk for colorectal cancer. Recommendations regarding treatment of low-grade dysplasia (LGD) indicate an individualized approach between colectomy and surveillance. We present a unique case of a patient with ulcerative colitis who had multifocal LGD on 2 consecutive colonoscopies. However, after 10 years and 16 surveillance colonoscopies, she had no further evidence of dysplasia. This appears to be the first case of proven, permanently resolved multifocal LGD in inflammatory bowel disease that challenges our understanding of the natural history of LGD.